2012
DOI: 10.1021/ac301124r
|View full text |Cite
|
Sign up to set email alerts
|

Electroanalytical Performance of Nitrogen-Containing Tetrahedral Amorphous Carbon Thin-Film Electrodes

Abstract: Tetrahedral amorphous carbon (ta-C) consists of a mixture of sp(3)- and sp(2)-bonded carbon ranging from 60 to 40% (sp(3)/sp(3)+sp(2)) depending on the deposition conditions. The physical, chemical, and electrochemical properties depend on the sp(2)/sp(3) bonding ratio as well as the presence of incorporated impurities, such as hydrogen or nitrogen. The ability to grow ta-C at lower temperatures (25-100 °C) on a wider variety of substrates as compared to CVD diamond is an advantage of this material. Herein, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 49 publications
4
73
2
Order By: Relevance
“…Swain and coworkers demonstrated that the ΔEp of Fe(CN)6 4-was dependent upon the sp 3 content of the sp 2 and sp 3 mixed carbon films. 19 On the other hand, it is well known that average roughness, surface oxygen-containing groups and wettability often influence the electron transfer rates for some redox species. However, the average roughness, O/C ratio and contact angle of N-UBM film electrodes remained almost unchanged, as summarized in Table 1.…”
Section: Potential Window and Basic Electrochemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Swain and coworkers demonstrated that the ΔEp of Fe(CN)6 4-was dependent upon the sp 3 content of the sp 2 and sp 3 mixed carbon films. 19 On the other hand, it is well known that average roughness, surface oxygen-containing groups and wettability often influence the electron transfer rates for some redox species. However, the average roughness, O/C ratio and contact angle of N-UBM film electrodes remained almost unchanged, as summarized in Table 1.…”
Section: Potential Window and Basic Electrochemical Propertiesmentioning
confidence: 99%
“…[26][27][28][29][30] However, very few reports studied the relationship between carbon film structures, particularly about chemical bonds and electrocatalytic properties. 9,19 In this work, we studied N-UBM nanocarbon film electrodes with relatively low nitrogen concentration in terms of structural dependence of ORR. Figure 5 shows voltammograms of oxygen reduction at pure-UBM and N-UBM nanocarbon film (N = 0, 1.8, 6.4, 7.8, and 10.9 at%) electrodes.…”
Section: Electrocatalytic Reduction Of Oxygenmentioning
confidence: 99%
“…It has been known that the radius of nitrogen atom is very close to that of carbon atom, so nitrogen is very preferable spices for doping agent with carbon. Nitrogen can be doped with carbon nanotube to increase the electronic quantum transport properties [8] energy and catalytic applications [9,10], nano-devices [11] and electro-analytical performance [12]. Nitrogen being a gaseous phase has the advantage of better control of dopant concentration in a-C films, and the incorporation of nitrogen can strongly decrease the defect density, which gives prospects on its use as a semiconductor material [13] for different energy related applications.…”
Section: Introductionmentioning
confidence: 99%
“…We also investigated the electron transfer rate with Fe(CN) 6 3-/4-on the basis of previous reports. 34,46,47 This is because an edge plane contributes more to the reduction of the target metals than a basal plane in ASV measurements. 48 The electron transfer rate constant (k0) on UBM (50:50) was about 4.5-times smaller than that of UBM (80:20) (Table 3).…”
Section: Properties Of Ubm Nanocarbon Filmmentioning
confidence: 99%